Genomic Survey and Expression Analysis of GLKs in Watermelon (Citrullus lanatus) - Qiangqiang Ding; Li Jia; Xiangting Jiang; Mingxia Wang; Yan Wang; Haikun Jiang; Feifei Yu; Congsheng Yan (Horticulturae, 2023)
Golden2-like (GLK) genes positively regulate chloroplast development, increase crop yields, and improve fruit quality. However, there has been no comprehensive identification and characterization of GLKs in watermelon. In this study, a total of 48 ClGLKs were identified in the watermelon genome. Based on phylogenetic analysis, they were divided into five groups. ClGLKs within the same group showed a similar gene structure and conserved motif compositions. Promoter analysis indicated that cis-elements responsive to light were the most abundant, though cis-elements associated with hormones, stress, and developmental regulation were also identified in ClGLKs promoters. Expression analysis indicated significant responses of some ClGLKs to drought and CGMMV stress, suggesting that these genes may participate in responses to biotic and abiotic stresses. Phenotypic analyses revealed enhanced chloroplast development and increased thylakoid density and chlorophyll content in the pericarp of a “dark green” watermelon cultivar. ClGLK8 was identified as the homolog of GLK1-2, the genes that promote chloroplast development and chlorophyll biosynthesis in fruits, and showed significantly increased expression in accordance with chloroplast development and chlorophyll accumulation. Our results provide detailed knowledge of the ClGLKs, which will enhance efforts to further improve the fruit quality of watermelon.